Modigiz Application as an Educational Media for Overweight Teenagers - Retno Wahyu Ningsih; Joyeti Darni; Ramadan Wibi Surya Aji (Poltekkes Kemenkes Mataram, 2023)
Background: Android mobile applications about nutrition and health are starting to be developed, but only a few develop mobile applications with a discussion of overweight adolescents. Android media with exciting features can be an alternative to increase adolescents' awareness of the problem of obesity.Research Methods: Development of an Android mobile application named